Biology and demographic statistics of the green leafhopper (Nephotettix virescens Distant) as the main vector of tungro virus in tungro-resistant rice varieties - Hutasoit, Rudi Tomson; Widiarta, I Nyoman; Jihad, Muhammad; Sitorus, Alfonso; Susilawati, Susilawati; Puspitasari, Mahardika (Universitas Lampung, 2025)
Tungro disease is one of the major constraints to rice production in Indonesia. Although tungro-resistant rice varieties have proven effective in reducing the spread of the virus, it is essential to consider their impact on the development of vector insect populations. This study aims to investigate the biology and demographic characteristics of Nephotettix virescens Distant on various tungro-resistant rice varieties. The research was conducted by maintaining and observing the development of N. virescens on the tungro-resistant varieties Inpari 7, Inpari 8, Inpari 9, Inpari 36, and Inpari 37, as well as the susceptible variety Taichung Native 1 (TN 1), under controlled environmental conditions with regulated temperature and humidity. Development was observed daily until the last individual died. The results indicated that the life cycle, longevity, and lifespan of N. virescens maintained on tungro-resistant varieties differed significantly from those on the susceptible variety TN 1. The life cycle of N. virescens on Inpari 7, Inpari 8, Inpari 9, Inpari 36, and Inpari 37 was 27.57, 30.50, 27.60, 30.80, and 31.64 days, respectively, whereas on the susceptible variety TN 1, it lasted only 24.94 days. Demographic statistical analysis revealed that the net reproductive rate (R?) and intrinsic rate of increase (r) of N. virescens maintained on tungro-resistant varieties were lower than those on the susceptible variety TN 1. Additionally, these tungro-resistant varieties resulted in a longer generation time (T) and doubling time (DT). Consequently, the tungro-resistant varieties negatively affected the vector by prolonging its life cycle, increasing the average generation time (T) and doubling time (DT), and reducing both the net reproductive rate (R?) and the intrinsic rate of increase (r). These five varieties can be considered as options for varietal rotation to suppress the growth of insect vector populations and limit the spread of the tungro virus, especially in tungro-endemic areas.